Maternal and fetal outcomes following exposure to duloxetine in pregnancy: cohort study. (19th February 2020) - Huybrechts, Krista F; Bateman, Brian T; Pawar, Ajinkya; Bessette, Lily G; Mogun, Helen; Levin, Raisa; Li, Hu; Motsko, Stephen; Scantamburlo Fernandes, Maria Fernanda; Upadhyaya, Himanshu P; Hernandez-Diaz, Sonia
Abstract: Objective: To evaluate the risk of adverse maternal and infant outcomes following in utero exposure to duloxetine. Design: Cohort study nested in the Medicaid Analytic eXtract for 2004-13. Setting: Publicly insured pregnancies in the United States. Participants: Pregnant women 18 to 55 years of age and their liveborn infants. Interventions: Duloxetine exposure during the etiologically relevant time window, compared with no exposure to duloxetine, exposure to selective serotonin reuptake inhibitors, exposure to venlafaxine, and exposure to duloxetine before but not during pregnancy. Main outcome measures: Congenital malformations overall, cardiac malformations, preterm birth, small for gestational age infant, pre-eclampsia, and postpartum hemorrhage. Results: Cohort sizes ranged from 1.3 to 4.1 million, depending on the outcome. The number of women exposed to duloxetine varied by cohort and exposure contrast and was around 2500-3000 for early pregnancy exposure and 900-950 for late pregnancy exposure. The base risk per 1000 unexposed women was 36.6 (95% confidence interval 36.3 to 36.9) for congenital malformations overall, 13.7 (13.5 to 13.9) for cardiovascular malformations, 107.8 (107.3 to 108.3) for preterm birth, 20.4 (20.1 to 20.6) for small for gestational age infant, 33.6 (33.3 to 33.9) for pre-eclampsia, and 23.3 (23.1 to 23.4) for postpartum hemorrhage. After adjustment for measured potential confounding variables, all baseline characteristics were well balanced for all exposure contrasts. In propensity score adjusted analyses versus unexposed pregnancies, the relative risk was 1.11 (95% confidence interval 0.93 to 1.33) for congenital malformations overall and 1.29 (0.99 to 1.68) for cardiovascular malformations. For preterm birth, the relative risk was 1.01 (0.92 to 1.10) for early exposure and 1.19 (1.04 to 1.37) for late exposure. For small for gestational age infants the relative risks were 1.14 (0.92 to 1.41) and 1.20 (0.83 to 1.72) for early and late pregnancy exposure, respectively, and for pre-eclampsia they were 1.12 (0.96 to 1.31) and 1.04 (0.80 to 1.35). The relative risk for postpartum hemorrhage was 1.53 (1.08 to 2.18). Results from sensitivity analyses were generally consistent with the findings from the main analyses. Conclusions: On the basis of the evidence available to date, duloxetine is unlikely to be a major teratogen but may be associated with an increased risk of postpartum hemorrhage and a small increased risk of cardiac malformations. While continuing to monitor the safety of duloxetine as data accumulate over time, these potential small increases in risk of relatively uncommon outcomes must be weighed against the benefits of treating depression and pain during pregnancy in a given patient. Trial registration: EUPAS 15946.